Lipid Tetrad Index as a Predictive Marker for Coronary Artery Disease in Type 2 Diabetes Patients (International Journal of Environmental Sciences, 2025)
Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality in type 2 diabetes mellitus (T2DM). As conventional lipid parameters may underestimate atherogenic risk, this study aimed to compare lipoprotein(a) [Lp(a)] levels and lipid tetrad index (LTI) between T2DM patients with and without CAD and assess their correlation with standard lipid parameters.Methods: This cross sectional comparative study was conducted at a tertiary care hospital over a period of 18 months. The study included 128 participants, equally divided between cases (diabetic patients with coronary artery disease) and controls (diabetic patients without coronary artery disease). Comprehensive data on lipid markers, including total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and LTI, were collected. Statistical analysis comprised t-tests for mean comparisons and chi-square tests for categorical variables.Results: Diabetic patients exhibited significantly higher levels of TC (218.77 ± 39.80 mg/dL vs. 163.66 ± 16.68 mg/dL, p < 0.001), TG (192.39 ± 54.76 mg/dL vs. 112.39 ± 42.72 mg/dL, p < 0.001), LDL (140.12 ± 37.59 mg/dL vs. 99.61 ± 19.91 mg/dL, p < 0.001), and lipoprotein(a) (11.56 ± 2.18 mg/dL vs. 8.41 ± 2.47 mg/dL, p < 0.001) compared to controls. HDL levels were lower in diabetic patients (40.67 ± 5.07 mg/dL vs. 44.19 ± 6.73 mg/dL, p = 0.001). LTI was significantly higher in cases, showing better predictive accuracy than traditional lipid parameters. It correlated strongly with TC, TG, LDL, and Lp(a), and was associated with hypertension, and poor glycemic control.Conclusion: T2DM patients with CAD exhibited a significantly more atherogenic lipid profile and higher LTI values than those without CAD. LTI showed strong correlations with key lipid parameters, supporting its role as a comprehensive and cost-effective marker for cardiovascular risk assessment in diabetic populations.